Design, Development, and Testing of an Indigenous Knowledge Management System Using Mobile Device Video Capture and Web 2.0 Protocols - Flor, Alexander G.; Amoloza, Emely M.; Flor Jr., Alexander Benjamin (International Journal on Open and Distance e-Learning, 2019)
This study attempted to answer the following research questions: How can mobile devices be used by rural communities to document indigenous knowledge? How can Web 2.0 protocols be employed in an indigenous knowledge management system? How will indigenous peoples (IPs) respond to the use of mobile technology in the documentation of their local knowledge? The theoretical basis for proposing that mobile devices may lead to the active participation of rural communities and indigenous peoples as ICT4D Web content providers is founded on three concepts: social capital; the network effect; and critical mass theory. The primary technological intervention was the mobile device. GPRS enabled mobile phones, with audio-video capture and Internet browsing functionalities were provided to focal persons from three IP groups. The Principal Investigator trained the focal persons on mobile phone video capture of indigenous or local knowledge. A content management system was designed to contain indigenous or local knowledge in agriculture in the form of rituals, practices, and others. The Principal Investigator and his assistants observed the knowledge capture and utilization process. During the conduct of the study, however, the researcher observed a marked reluctance from organized indigenous people’s groups to participate in the initiative. It soon became apparent that interfacing indigenous knowledge with Web 2.0 and open access concepts held complicated issues. The intervening variables observed and deduced by the Principal Investigator were: indigenous belief systems; privacy of indigenous peoples; indigenous knowledge system (IKS) protocols; the significance of context in IKS; prejudice and value judgments among non-IP users; and misrepresentation of indigenous knowledge.